2014
DOI: 10.1002/anie.201408910
|View full text |Cite
|
Sign up to set email alerts
|

Unified Total Syntheses of (−)‐Medicarpin, (−)‐Sophoracarpan A, and (±)‐Kushecarpin A with Some Structural Revisions

Abstract: The total syntheses of medicarpin, sophoracarpan A, and kushecarpin A from a common intermediate are achieved by using ortho- and para-quinone methide chemistry. Additionally, the relative stereochemistry of sophoracarpan A and B have been reassigned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 44 publications
0
26
0
1
Order By: Relevance
“…Based on the spectroscopic data and comparisons with the data found in the literature, the known compounds were identified as 8-prenylmilldurone ( 3 ) [22], 6-methoxycalpogonium isoflavone A ( 8 ) [23], durmillone ( 9 ) [24], durallone ( 10 ) [25], ichthynone ( 11 ) [8], millesianin C ( 12 ) [26], toxicarol isoflavone ( 13 ) [27], cladrastin ( 14 ) [28], dalpatein ( 15 ) [29], 7-hydroxy-2′,4′,5′,6-tetramethoxyisoflavone ( 16 ) [30], 3,9-dihydroxypterocarp-6a-en ( 17 ) [31], dehydromaackiain ( 18 ) [32], flemichapparin B ( 19 ) [33], (−)-medicarpin ( 20 ) [34], (−)-maackiain ( 21 ) [35], (−)-variabilin ( 22 ) [36], (−)-pisatin ( 23 ) [37], dalbinol ( 32 ) [38], (−)-sativin ( 25 ) [39], (−)-dehydrodiconiferyl alcohol ( 26 ) [40], (+)-vomifoliol ( 27 ) [41], and dihydrophaseic acid ( 28 ) [42].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the spectroscopic data and comparisons with the data found in the literature, the known compounds were identified as 8-prenylmilldurone ( 3 ) [22], 6-methoxycalpogonium isoflavone A ( 8 ) [23], durmillone ( 9 ) [24], durallone ( 10 ) [25], ichthynone ( 11 ) [8], millesianin C ( 12 ) [26], toxicarol isoflavone ( 13 ) [27], cladrastin ( 14 ) [28], dalpatein ( 15 ) [29], 7-hydroxy-2′,4′,5′,6-tetramethoxyisoflavone ( 16 ) [30], 3,9-dihydroxypterocarp-6a-en ( 17 ) [31], dehydromaackiain ( 18 ) [32], flemichapparin B ( 19 ) [33], (−)-medicarpin ( 20 ) [34], (−)-maackiain ( 21 ) [35], (−)-variabilin ( 22 ) [36], (−)-pisatin ( 23 ) [37], dalbinol ( 32 ) [38], (−)-sativin ( 25 ) [39], (−)-dehydrodiconiferyl alcohol ( 26 ) [40], (+)-vomifoliol ( 27 ) [41], and dihydrophaseic acid ( 28 ) [42].…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, the enantioselectivity was unaffected by the additional substituent, with the reactions giving 10 e and 10 f in good yields and enantioselectivity. It is expected that subsequent debromination of these products would give access to 3,4‐disubstituted p ‐quinols, which are valuable intermediates in natural product synthesis,,, but are still hard to synthesize through state‐of‐the‐art asymmetric catalysis …”
Section: Figurementioning
confidence: 99%
“…24 The cis ring-fusion obtained by using this protocol contrasts with the trans ring fusion obtained by the Zhao group 18 and the List group 19 for related reactions promoted by Brønsted acid catalysts (see Scheme 6). Only the cis stereochemistry is found in known natural products (e.g., flavonoids: lophirone H 26 and cordigol; 27 and pterocarpan isoflavonoids: medicarpin 28 and phaseolin 29 ), and in 2017 we reported the use of the SnCl 4 -mediated reaction as a key step in the synthesis of the pentaphenolic Lophira lanceolate extract, lophirone H. 25 DFT calculations suggested that the oxonium Prins pathway was lower in energy than the…”
Section: Stepwise Addition Reactionsmentioning
confidence: 96%
“…The Pettus group have been key players in the field of natural product synthesis using oQMs, having reported >10 completed syntheses using these as key reactive intermediates. 28,[33][34][35][36][37][38][39] Following on from their earlier work on the total synthesis of natural heliananes via a diastereoselective HDA reaction between an enol ether and an oQM species, 40 in 2012 they disclosed their efforts to synthesize heliol (Scheme 11). 41 Scheme 11 Total synthesis of (±)-heliol via an acid-catalyzed, stepwise cyclocondensation reaction to form the oQM 41 An acid-cataled, stepwise, cyclocondensation reaction was used to generate the oQM intermediate which was then trapped in an intramolecular fashion by the prenyl residue, thereby forming the 2-oxabicyclo[3.3.1]nonane skeleton found in the product.…”
Section: Applications In Total Synthesismentioning
confidence: 99%